2020
DOI: 10.1159/000509938
|View full text |Cite
|
Sign up to set email alerts
|

Collapsing Glomerulopathy Affecting Native and Transplant Kidneys in Individuals with COVID-19

Abstract: Since the emergency of novel coronavirus COVID-19 (SARS-CoV-2) in December 2019, infections have spread rapidly across the world. The reported incidence of acute kidney injury (AKI) in the context of COVID-19 is variable, and its mechanism is not well understood. Data are emerging about possible mechanisms of AKI including virus-induced cytopathic effect and cytokine storm-induced injury. To date, there have been few reports of kidney biopsy findings in the context of AKI in COVID-19 infection. This article de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 16 publications
1
34
0
1
Order By: Relevance
“…Eleven samples were from autopsied kidneys (9, 81, 82) and only 5 from kidney biopsies performed in live patients, the latter, were all in patients who were subsequently diagnosed with collapsing glomerulopathy (35)(36)(37)(38).…”
Section: Evidence For and Against Sars-cov-2 In The Kidney From Patients With Covid-19mentioning
confidence: 99%
“…Eleven samples were from autopsied kidneys (9, 81, 82) and only 5 from kidney biopsies performed in live patients, the latter, were all in patients who were subsequently diagnosed with collapsing glomerulopathy (35)(36)(37)(38).…”
Section: Evidence For and Against Sars-cov-2 In The Kidney From Patients With Covid-19mentioning
confidence: 99%
“…Case reports, small case series, and autopsy studies have shown a wide spectrum of kidney manifestations in COVID-19 patients and have improved our understanding of kidney disease in this population. Reported manifestations in native biopsies include acute tubular injury (ATI) 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , myoglobin cast nephropathy 7 , thrombotic microangiopathy (TMA) 9 , 16 , 20 , 25 , 26 , 27 ; acute interstitial nephritis 14 , 28 , non-collapsing focal and segmental glomerulosclerosis (FSGS) 9 , 19 , 20 , 29 , collapsing glomerulopathy (also known as COVID-19 associated nephropathy, COVAN) 7 , 8 , 9 , 15 , 20 , 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , membranous nephropathy 8 , 20 , 42 , minimal change disease 48 , 49 , 50 , 48 , 49 , 50 , 48 , …”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only 15 kidney allograft biopsy findings from COVID‐19‐infected transplant recipients have been published as case reports ( n = 9) or as part of series containing predominantly native kidney biopsies ( n = 6). 1 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 These reports (summarized in Table S1 ) demonstrate a variety of etiologies of allograft dysfunction in the transplanted kidney, including podocytopathies, 6 , 9 , 10 , 11 , 12 , 13 acute rejection, 1 , 15 allograft infarction, 14 thrombotic microangiopathy (TMA), 7 and acute tubular injury (ATI). 1 , 8 , 15 Direct viral invasion of kidney parenchyma was suggested in two reported cases.…”
Section: Introductionmentioning
confidence: 99%